Bimetal‐organic Framework‐derived Co9S8/ZnS@NC Heterostructures for Superior Lithium‐ion Storage. Issue 10 (21st April 2020) - Duan, Junfei; Wang, Yongkang; Li, Hongxing; Wei, Donghai; Wen, Fang; Zhang, Guanhua; Liu, Piao; Li, Lingjun; Zhang, Wei‐bing; Chen, Zhaoyong
Abstract: Heterostructure engineering of electrode materials, which is expected to accelerate the ion/electron transport rates driven by a built‐in internal electric field at the heterointerface, offers unprecedented promise in improving their cycling stability and rate performance. Herein, carbon nanotubes with Co9 S8 /ZnS heterostructures embedded in a N‐doped carbon framework (Co9 S8 /ZnS@NC) have been rationally designed via an in‐situ vapor chemical transformation strategy with the aid of thiophene, which not only acted as carbon source for the growth of carbon nanotubes but also as sulfur source for the sulfurization of metal Zn and Co. Density functional theory (DFT) calculation shows an about 3.24 eV electrostatic potential difference between ZnS and Co9 S8, which results in a strong electrostatic field across the interface that makes electrons transfer from Co9 S8 to the ZnS side. As expected, a stable cycling performance with reversible capacity of 411.2 mAh g −1 at 1000 mA g −1 after 300 cycles, excellent rate capability (324 mAh g −1 at 2000 A g −1 ) and a high percentage of pseudocapacitance contribution (87.5% at 2.2 mv/s) for lithium‐ion batteries (LIBs) are achieved. This work provides a possible strategy for designing multicomponent heterostructural materials for application in energy storage and conversion fields. Abstract : Co9 S8 /ZnS heterostructures were fabricated via pyrolysis of a bimetal Zn−Co−MOF precursor with thiophene vapor bubbled simultaneously with nitrogen carrier gas. Due to the strong carrier‐transfer rate at the hetero‐interface between Co9 S8 and ZnS, as verified by DFT calculation, the Co9 S8 /ZnS electrode showed stable cycling performance and excellent rate capability. This study might provide a rational strategy for the design of other heterostructural composites for application in energy storage and conversion fields.